2004
DOI: 10.5483/bmbrep.2004.37.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Some Hepatic Enzymes in Schistosomiasis and Concomitant Alteration of Arylsulfatase B

Abstract: The levels of arylsulfatases A and B, α-amylase, aspartate transcarbamylase, and γ-glutamyl transpeptidase were investigated during the infection of mice with schistosoma mansoni. This infection caused a significant (p<0.001) increase in the activity of hepatic arylsulfatase B (ASB), aspartate transcarbamylases and γ-glutamyl transpeptidase. A non-significant difference occurred for α-amylase (p<0.3) and arylsulfatase A (p>0.5) when compared to the control. The specific activity of hepatic ASB was progressivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…The molecular weight of the ASB band was about 60 KDa. The enzyme was purified to the extent previously described for the enzyme from the control and Schistosoma-infected mouse [10]. The observed K m values of the enzyme toward PNCS are 3.50^0.30 and 3.0^0.40 mM in control and infected cases, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The molecular weight of the ASB band was about 60 KDa. The enzyme was purified to the extent previously described for the enzyme from the control and Schistosoma-infected mouse [10]. The observed K m values of the enzyme toward PNCS are 3.50^0.30 and 3.0^0.40 mM in control and infected cases, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Arylsulfatase B (ASB, EC 3.1.6.9), is a lysosomal hydrolase, which desulfates the non-reducing terminal N-acetylgalactosamine-4-sulfate residues present in glycosaminoglycan [14]. Since this enzyme is significantly increased in schistosomiasis [10] and its properties in this disease is still obscure, the present study was undertaken to investigate the interaction of some drugs that are used for the treatment of schistosomiasis with this enzyme. The effect of drugs in vitro on the purified enzyme from the liver of the infected mouse is examined to find their influence on its catalytic and immunological properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of S. mansoni infection and administration of the schistosomicidal drugs on the activities of beta glucuronidase, acid ribonuclease, and alpha-naphthyl acteate esterase may be considered as indices for carcinogenicity [11]. Recently, it was described that praziquantel inhibits hepatic arylsulfatase B from Schistosoma-infected mice in a mixed-type inhibition [4]. The data of the present study revealed that SCR has a decreased activity in the liver of S. mansoni-infected mouse and the confirmed schistosomicidal drugs for the treatment of the disease have an in vitro inhibition of this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that serum GGT in advanced cases of Schistosma mansoni infection was significantly increased [10] due to its effect on the liver. The alteration of GGT activity in schistosomiasis might be attributed to enzyme regulation and modifications [11]. The significant change of GGT in the liver may be an indication of altered degradation of glutathione and the formation of γ-glutamyl-amino acids [1].…”
mentioning
confidence: 99%